Survival associated with extent of radical hysterectomy in early-stage cervical cancer: a subanalysis of the Surveillance in Cervical CANcer (SCCAN) collaborative study - Bizzarri, Nicolò; Querleu, Denis; Dostálek, Lukáš; van Lonkhuijzen, Luc R C W; Giannarelli, Diana; Lopez, Aldo; Salehi, Sahar; Ayhan, Ali; Kim, Sarah H; Ortiz, David Isla; Klat, Jaroslav; Landoni, Fabio; et al. (American journal of obstetrics and gynecology, 2023)
BACKGROUND: International guidelines recommend tailoring the radicality of hysterectomy according to the known preoperative tumor characteristics in patients with early-stage cervical cancer. OBJECTIVE: This study aimed to assess whether increased radicality had an effect on 5-year disease-free survival in patients with early-stage cervical cancer undergoing radical hysterectomy. The secondary aims were 5-year overall survival and pattern of recurrence. STUDY DESIGN: This was an international, multicenter, retrospective study from the Surveillance in Cervical CANcer (SCCAN) collaborative cohort. Patients with the International Federation of Gynecology and Obstetrics 2009 stage IB1 and IIA1 who underwent open type B/C1/C2 radical hysterectomy according to Querleu-Morrow classification between January 2007 and December 2016, who did not undergo neoadjuvant chemotherapy and who had negative lymph nodes and free surgical margins at final histology, were included. Descriptive statistics and survival analyses were performed. Patients were stratified according to pathologic tumor diameter. Propensity score match analysis was performed to balance baseline characteristics in patients undergoing nerve-sparing and non-nerve-sparing radical hysterectomy. RESULTS: A total of 1257 patients were included. Of note, 883 patients (70.2%) underwent nerve-sparing radical hysterectomy, and 374 patients (29.8%) underwent non-nerve-sparing radical hysterectomy. Baseline differences between the study groups were found for tumor stage and diameter (higher use of non-nerve-sparing radical hysterectomy for tumors >2 cm or with vaginal involvement; P<.0001). The use of adjuvant therapy in patients undergoing nerve-sparing and non-nerve-sparing radical hysterectomy was 27.3% vs 28.6%, respectively (P=.63). Five-year disease-free survival in patients undergoing nerve-sparing vs non-nerve-sparing radical hysterectomy was 90.1% (95% confidence interval, 87.9-92.2) vs 93.8% (95% confidence interval, 91.1-96.5), respectively (P=.047). Non-nerve-sparing radical hysterectomy was independently associated with better disease-free survival at multivariable analysis performed on the entire cohort (hazard ratio, 0.50; 95% confidence interval, 0.31-0.81; P=.004). Furthermore, 5-year overall survival in patients undergoing nerve-sparing vs non-nerve-sparing radical hysterectomy was 95.7% (95% confidence interval, 94.1-97.2) vs non-nerve-sparing 96.5% (95% confidence interval, 94.3-98.7), respectively (P=.78). In patients with a tumor diameter ≤20 mm, 5-year disease-free survival was 94.7% in nerve-sparing radical hysterectomy vs 96.2% in non-nerve-sparing radical hysterectomy (P=.22). In patients with tumors between 21 and 40 mm, 5-year disease-free survival was 90.3% in non-nerve-sparing radical hysterectomy vs 83.1% in nerve-sparing radical hysterectomy (P=.016) (no significant difference in the rate of adjuvant treatment in this subgroup, P=.47). This was confirmed after propensity match score analysis (balancing the 2 study groups). The pattern of recurrence in the propensity-matched population did not demonstrate any difference (P=.70). CONCLUSION: For tumors ≤20 mm, no survival difference was found with more radical hysterectomy. For tumors between 21 and 40 mm, a more radical hysterectomy was associated with improved 5-year disease-free survival. No difference in the pattern of recurrence according to the extent of radicality was observed. Non-nerve-sparing radical hysterectomy was associated with better 5-year disease-free survival than nerve-sparing radical hysterectomy after propensity score match analysis.
Keywords: těhotenství; hysterektomie; Neoplasm Staging; Uterine Cervical Neoplasms; spinocelulární karcinom; lidé; radicality; survival; Hysterectomy; cervical cancer; Female; retrospektivní studie; Humans; staging nádorů; radical hysterectomy; Carcinoma, Squamous Cell; přežití bez známek nemoci; early stage; Disease-Free Survival; Pregnancy; ženské pohlaví; nádory děložního čípku; surgery; laparotomy; Retrospective Studies